Impact of long‐term administration of maralixibat on children with cholestasis secondary to Alagille syndrome - Benjamin L. Shneider; Catherine A. Spino; Binita M. Kamath; John C. Magee; Rosalinda V. Ignacio; Suiyuan Huang; Simon P. Horslen; Jean P. Molleston; Alexander G. Miethke; Rohit Kohli; Daniel H. Leung; M. Kyle Jensen; et al. (Hepatology Communications, 2022)
Abstract There is growing interest in, but limited data about, intestinal bile acid transport inhibitors as treatment for cholestatic liver disease. The current analyses combine two similar randomized placebo‐controlled trials with subsequent extension phases investigating the impact of maralixibat in children with severe cholestasis secondary to Alagille Syndrome (n = 57). The primary outcomes were measures of pruritus (ItchRO[Obs]) and clinician scratch scale (CSS), both increasing in severity from 0 to 4) and quality of life (QoL) (Parent PedsQL and Multidimensional Fatigue Scale module [MFS] scaled 0–100 with increased QoL) at week 48 of the extension phase relative to the baseline of the placebo‐controlled trials (week 13). Secondary assessments included other clinical and biochemical parameters assessed in participants at week 72 or end of treatment (after week 48). At week 48, statistically and clinically significant least square mean (95% CI) improvements in pruritus and QoL were observed (ItchRO[Obs] −1.59 [−1.81, −1.36], CSS −1.36 [−1.67, −1.05], PedsQL +10.17 [4.48, 15.86], and multidimension fatigue [MFS] +13.97 [7.85, 20.08]). At week 48, serum bile acids, platelet count, and cholesterol decreased, whereas alanine aminotransferase (ALT) increased and total bilirubin (TB) and albumin were stable. Changes were durable at week 72 and end of treatment. There were no deaths; 2 participants underwent liver transplantation. Study drug was discontinued in 9 participants after treatment‐emergent adverse events, 6 of which were events of increased ALT or TB. Conclusion: Maralixibat administration was associated with marked improvement in pruritus and QoL. Interpretation of these findings is complicated by the complex natural history of severe cholestasis in Alagille syndrome.